Enhancing theological education's viability through clergy graduate's work performance input reference for a five-year development plan. - Juan, Jr., Guillermo, 1962- (Quezon City : Trinity College, 2002)
Cognizant of the effects wrought by change, this study aims to determine the viability of the theological education programs of St. Andrew's Theological Seminary and Aglipay Central Theological Seminary as institutions of theological education, training, and ministerial formation through the work performance of their clergy graduates serving the Iglesia Filipina Independiente, with the hope that the results of this study will serve as an initial step in reshaping and improving the orientation and direction of the theological education programs of the IFI seminarians.
In partial fulfillment of the requirements for the degree Doctor of Education
A dissertation presented to the faculty of the Graduate School, Trinity College of Quezon City
Dissertation (D. Ed.) - Trinity College of Quezon City
Keywords: Educational management